Face name matching and memory complaints in Parkinson’s disease - Siquier, Antònia; Andrés, Pilar (Frontiers in Psychology, 2022)
Objective. Memory impairment is a hallmark cognitive deficit in Parkinson’s disease (PD). However, it remains unclear which processes underlie this deficit in PD. Also, little is known on these patients’ subjective experiences of memory difficulties and their relationship with objective measures. We aim to portray memory deficits in PD by combining objective and subjective memory measures. Methods. Fifteen PD patients and 15 controls were assessed with an extended version of the Face-Name Associative Memory Exam (FNAME) and the Memory Failures of Everyday Questionnaire (MFE-28). We also explored the relationship among clinical and cognitive variables. Results. Participants with PD presented with more memory complaints. On the FNAME, these patients exhibited lower performance in free recall, as well as in name recognition and matching. Importantly, when controlling for initial learning, group effects disappeared, except for matching. Associative memory therefore was significantly compromised in PD and correlated with subjective memory complaints. Conclusions. Our findings suggest that associative memory may constitute a sensitive measure to detect subtle memory deficits in PD. Moreover, the current study further clarifies the source of memory impairment in PD. Thus, our study highlights the clinical value of including associative memory tests such as the FNAME in PD neuropsychological assessment.